The Use of English Podcast among English Education Students at Universitas Negeri Padang - Velia Yuda Gusfira; Nofrina Eka Putri (Journal of English Language Teaching, 2022)
Technological developments have changed human life, including the education sector. Currently, many technology-based learning media have been found, podcast is one of them. Podcasts can be used as an additional learning media, especially for listening and speaking activities. This study aims to see the phenomenon of using English podcast among English Education students at Universitas Negeri Padang and explore their perception about the use of podcast to improve their listening and speaking skills. This study used a qualitative research method with a case study approach. The questionnaire and interview are used to collect the data. In general, there are not many of podcast users among English Education students at Universitas Negeri Padang, especially English podcasts. The data shows that only about 13% of English Education students use podcasts, of which 7% use English podcasts. Based on this data, students who use English podcasts agree that English podcasts can be used as additional learning media that can improve their listening and speaking skills. However, students also found their own challenges when listening to English podcasts, namely words, idioms or slang that are unfamiliar to them and also internet network problems